2010
DOI: 10.1038/ng.571
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analyses identify multiple loci associated with smoking behavior

Abstract: Consistent but indirect evidence has implicated genetic factors in smoking behavior1,2. We report meta-analyses of several smoking phenotypes within cohorts of the Tobacco and Genetics Consortium (n = 74,053). We also partnered with the European Network of Genetic and Genomic Epidemiology (ENGAGE) and Oxford-GlaxoSmithKline (Ox-GSK) consortia to follow up the 15 most significant regions (n > 140,000). We identified three loci associated with number of cigarettes smoked per day. The strongest association was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
644
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,072 publications
(686 citation statements)
references
References 37 publications
28
644
4
1
Order By: Relevance
“…We also confirmed the associations between this variance and incident COPD 4, 13, 14, tobacco‐related cancers 7, 15, 16, lung cancer 4, 7, 15, 17, 18, 19, 20, 21 and smoking quantity 2, 3, 7, indicating an exciting overlap of genetic influence on ND and smoking‐related diseases. As mentioned above, this region of the nAChRs is characterized by high correlation and the results should be interpreted as an association with the cluster instead of the rs1051730.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We also confirmed the associations between this variance and incident COPD 4, 13, 14, tobacco‐related cancers 7, 15, 16, lung cancer 4, 7, 15, 17, 18, 19, 20, 21 and smoking quantity 2, 3, 7, indicating an exciting overlap of genetic influence on ND and smoking‐related diseases. As mentioned above, this region of the nAChRs is characterized by high correlation and the results should be interpreted as an association with the cluster instead of the rs1051730.…”
Section: Discussionsupporting
confidence: 74%
“…Negative health consequences such as cancer, heart disease, stroke and respiratory diseases are well‐known complications, and cigarette smoking is responsible for about 5 million deaths annually (Data from the World Health Organization). Recent genomewide association studies have shown convincing associations between a number of genetic variations and both nicotine dependence (ND) and smoking behaviour 2, 3, 4, 5, 6. The synonymous single nucleotide polymorphism (SNP) rs1051730 on chromosome 15q25, in the gene for the nicotinic acetylcholine receptor (nAChr) subunit CHRNA3, showed the strongest association.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene–exposure and gene–outcome associations were identified in the CCGC 8, TAG 15 and cotinine 16 consortia summary‐level data. Models 2 and 3 were included as sensitivity analyses, as recommended by Burgess and colleagues 14.…”
Section: Methodsmentioning
confidence: 99%
“…Recent association findings for nicotine dependence, smoking behavior, and smoking-related diseases implicate genetically derived individual differences [1][2][3][4][5]. Among several reports from genome-wide association studies (GWAS), nicotinic cholinergic receptor α (CHRNA3-CHRNA5, rs1051730 or rs667282) has been identified as a lung cancer susceptible locus [6][7][8].…”
Section: Introductionmentioning
confidence: 99%